2022
DOI: 10.3389/fmolb.2022.895746
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Detection of the Alternative Spliced Human Proteome Using Translatome Sequencing

Abstract: Alternative splicing (AS) isoforms create numerous proteoforms, expanding the complexity of the genome. Highly similar sequences, incomplete reference databases and the insufficient sequence coverage of mass spectrometry limit the identification of AS proteoforms. Here, we demonstrated full-length translating mRNAs (ribosome nascent-chain complex-bound mRNAs, RNC-mRNAs) sequencing (RNC-seq) strategy to sequence the entire translating mRNA using next-generation sequencing, including short-read and long-read tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Further research on uncharacterized proteins, especially those encoded by short-ORFs, showed that they were indeed involved in diverse biological processes, including but not limited to cell proliferation ( Galindo et al, 2007 ), DNA damage repair ( Slavoff et al, 2014 ), muscle activities ( Anderson et al, 2015 ; Nelson et al, 2016 ), cell signaling ( Chng et al, 2013 ), mRNA degradation ( D'Lima et al, 2017 ), and phagocytosis ( Pueyo et al, 2016 ). Therefore, uncharacterized proteins have attracted increasing attention in recent years, but systemic research on these proteins is still lacking ( Delcourt et al, 2018 ; Wu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further research on uncharacterized proteins, especially those encoded by short-ORFs, showed that they were indeed involved in diverse biological processes, including but not limited to cell proliferation ( Galindo et al, 2007 ), DNA damage repair ( Slavoff et al, 2014 ), muscle activities ( Anderson et al, 2015 ; Nelson et al, 2016 ), cell signaling ( Chng et al, 2013 ), mRNA degradation ( D'Lima et al, 2017 ), and phagocytosis ( Pueyo et al, 2016 ). Therefore, uncharacterized proteins have attracted increasing attention in recent years, but systemic research on these proteins is still lacking ( Delcourt et al, 2018 ; Wu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using human cell lines, RNC-seq demonstrated approximately two times higher estimation of protein isoforms compared to ribo-seq for the same number of valid reads ( 49 ). Sequencing technologies enabling longer reads enhance the detection of known and novel isoforms ( 49 ).…”
Section: Ribosome-nascent Chain Complex (Rnc-seq)mentioning
confidence: 99%
“…Using human cell lines, RNC-seq demonstrated approximately two times higher estimation of protein isoforms compared to ribo-seq for the same number of valid reads ( 49 ). Sequencing technologies enabling longer reads enhance the detection of known and novel isoforms ( 49 ). RNC-seq holds promise for studying circular RNAs (circRNAs) and their role during translation ( 50 ), with applications in detecting circRNAs bound to ribosomes in glioblastoma.…”
Section: Ribosome-nascent Chain Complex (Rnc-seq)mentioning
confidence: 99%